The Dynamics of Law and Culture Interaction in Supporting Local Economic Growth: An Ethnographic Analysis of Indigenous Communities in Papua - Praditya Amalia Shofa (Riviera Publishing, 2024)
The government has made efforts to realize prosperity for all Indonesian people, including indigenous Papuans. Local culture plays a key role in shaping consumer preferences, patterns of business behavior, and the use of economic resources, which are important in designing economic development strategies that match the values and needs of local communities. The purpose of this study is to determine and analyze the dynamics of legal and cultural interactions in supporting local economic growth in Papuan society. The research method uses a literature study method with a qualitative approach. The data collection technique involves searching, collecting, and reading various literature sources. Data were analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results show that the interaction between law and culture is crucial in supporting local economic growth in indigenous Papuan communities, with cultural values, traditions and social norms playing an important role in shaping local economic practices. The complexity in the interaction between Papuan customary law and formal state law highlights the challenges and opportunities in achieving harmony between the two to advance local economic growth. This research has implications for the importance of integration between state law and Papuan customary law in efforts to promote sustainable local economic growth. Thus, the resulting policies can be more effective in accommodating local economic interests without overriding existing local wisdom, so as to achieve a balance between economic development and cultural preservation.